The role of policlonal selected material for sustainable viticulture - Martins, Antero (2009)
Viticulture can be economically friendly using polyclonal selected material, which maintains the genetic variability within varieties and offers stable behaviour throughout different environments. In Portugal, we carried out a genetic selection that preserves this variability, with good production, good quality and good sanitary state of the vegetative material. To select polyclonal material from one variety, we sample plants in old vineyards and we plant an experimental population representative of its genetic variability. In this trial field we analyse several qualitative and agronomic characteristics, aiming to select the best 15 to 30 clones. This methodology enables to obtain polyclonal material after a four-year study. Up to now, we have already obtained polyclonal material from 60 of the main portuguese varieties. In this paper we analyse the advantages of this material for sustainable viticulture, when compared with clones.